Motivation of quantity surveyor in the Malaysian construction industry towards job satisfaction / Siti Azimah Jamhari and Husrul Nizam Husin @ Hussain - Jamhari, Siti Azimah; Husin @ Hussain, Husrul Nizam (2019)
Many people faces the problems and challenges in daily life especially in their works. Occupational stress is a major hazard for many workers. In addition, it will affect on their satisfaction of work and also cannot concentrate on task that they are on to. This will lead to less productivity of work and the organization performance. Therefore, this paper aim is to study on the motivation of quantity surveyor in Malaysia to improve job satisfaction. This research used quantitative method. 137 questionnaires were distributed among quantity surveyors in consultant firm at Selangor and 55 respondents was return back the questionnaires. The data then was analyzed by using SPSS. The result indicates that the top three (3) motivation factors are, the self-motivation, financial incentives provided by employer and also the fair pay to job scope. The result also shows that, most of the respondent has leak of satisfaction on the working hours, salary and bonus given and also non-financial incentives which need to be improve by the industry. Lastly, the finding from this study could assist current and future industry team to gain insight on important of motivational factors among employee to achieved job satisfaction at workplace that will lead to the improvement of the organization's performance.